Management of Viral Hepatitis: Clinical and Public Health Perspectives – A Consensus Statement - M Sherman; Casl Hapatitis Consensus Group (Canadian Journal of Gastroenterology)
The Canadian Liver Foundation convened a two-day conference in September 1996, at which experts from across Canada were invited to discuss various aspects of viral hepatitis and to issue guidelines to assist practitioners in caring for patients with these diseases. The proceedings of this conference were transcribed and submitted to all participants for approval before being submitted for publication. The views expressed in this article represent the consensus opinion of the group. Where there was significant difference of opinion this is explicitly stated, and opposing points of view are given.